Effect of the hole concentration on the polaronic mobility for the strongly interacting electrons. Issue 1 (1st March 2022) - Debnath, Debika; Chatterjee, Ashok
Abstract: The effective hopping of the polaron has been studied for different hole concentrations. Holstein-Hubbard model is used for the half-filled and less than half-filled cases. A series of canonical transformations are imposed on the generic Hamiltonian and considering the strongly interacting electrons, the transformed Hamiltonian has been reconstructed to an effective t-J model. Using the mean-filled Hartree-Fock approximation the electronic Hamiltonian has been solved with the Zuberev's Green function technique. The effective polaronic transport is found to be strongly dependent on the electron and hole concentration of the system.